Influence of a modified versus a typical microcycle periodization on the weekly external loads and match day readiness in elite academy soccer players - Douchet, T.; Christos, P.; Carling, C.; Babault, N. (Journal of Human Kinetics, 2024)
A typical weekly periodization strategy in soccer positions the most demanding sessions four and three days before the match-day (MD-4/MD-3). However, a modified periodization strategy could intersperse the two most demanding sessions with a low-load training session. This study aimed to investigate the impact of these periodizations on external loads and MD readiness. Twenty academy players were tested. The modified weekly periodization strategy included a low-load training session between the two most demanding sessions, while the typical periodization implemented them consecutively. Players wore a GPS and rated their perceived exertion (RPE) during the most demanding sessions. Players were also tested using a CMJ, a 20-m sprint, the Illinois agility test (IAT), and the Hooper questionnaire on MD-4 to obtain baseline values (CONTROL) and on the match-day (TEST). CONTROL values were similar during experimental weeks. During the second most demanding session, players covered greater distances for the modified versus the typical periodization in the 20-25 km/h (306.3 ± 117.1 m vs. 223.5 ± 92.2 m, p < 0.05) and >25 km/h speed zones (89.5 ± 44.8 m vs. 67.2 ± 44.5 m, p < 0.05). On the MD, CMJ, 20-m sprint, and IAT performances were similar between both periodizations. However, 10-m time (1.89 ± 0.10 s vs. 1.92 ± 0.09 s, p < 0.05) and the Hooper index score (7.90 ± 2.14 a.u. vs. 9.50 ± 3.44 a.u., p < 0.05) were significantly lower during the modified periodization strategy. A decreased training load session positioned between the most demanding sessions may be of interest in elite academy soccer players as it can lead to increased weekly external loads and readiness on the MD.